An ecological study of territoriality in four Cichlid species resident on rocky shores near Monkey Bay, Lake Malawi - Sharp, Bradley John (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1982)
This study centres on a diverse assemblage of epilithic algal grazing fish (17 cichlids and 2 cyprinids) found on the rocky shores near Monkey Bay, Lake Malawi. Diet overlap among these species is large, but competitive exclusion is apparently avoided by the species having different feeding structures, behaviour and distribution on the shore. In many respects the ecology and behaviour of the cichlid fishes inhabiting the rocky zones of Lake Malawi parallel those of coral reef fish. In both communities there are species which are highly territorial, resulting in resource subdivision and, in some cases, the development of algal gardens. As this behaviour has not been previously reported for cichlid species, this thesis describes the territoriality of the rock-dwelling cichlids of Monkey Bay, Lake Malawi, and poses three specific questions: 1. What is the function of territoriality? 2. How do the territorial species subdivide the space resource? 3. What prevents one species taking over all the available space? It is suggested that interspecific territoriality evolved in response to a shortage of food, and, at present, serves principally to defend an algal garden i.e. a food supply of high standing crop. The species studied are extremely site specific. The rocky shore is subdivided among the four species according to the rock configuration, size, algal mat composition and position on the shore, of the available sites. An experimental study of the space utilization of the two common territorial species, referred to as 'Pseudotropheus orange cheek' and 'Pseudotropheus aggressive', showed that suitable territory sites are in short supply and that these species are in competition for some sites. These results do not support those of Fryer (1959) who suggested that a superabundance of food enabled fish to coexist by sharing the same food resource. Indeed it now appears that a shortage of food may have been a major driving force during the recent evolution of the species studied.
Keywords: Cichlids -- Nyasa, Lake; Cichlids -- Behavior